2006
DOI: 10.1103/physrevb.74.045329
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of oscillator strength in Gaussian quantum dots: An energy flow from center-of-mass mode to internal modes

Abstract: The energy spectra and oscillator strengths of two, three and four electrons confined by a quasitwo-dimensional attractive Gaussian-type potential have been calculated for different strength of confinement ω and potential depth D by using the quantum chemical configuration interaction (CI) method employing a Cartesian anisotropic Gaussian basis set. A substantial red shift has been observed for the transitions corresponding to the excitation into the center-of-mass mode (CM). The oscillator strengths, concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 50 publications
0
36
0
Order By: Relevance
“…The anharmonicity of the Gaussian potential in Eq. (2) can be characterized as defined in a previous study [32] by the ratio of the confinement strength ω z over the depth of the Gaussian potential D as…”
Section: A Theoretical Modelmentioning
confidence: 99%
See 4 more Smart Citations
“…The anharmonicity of the Gaussian potential in Eq. (2) can be characterized as defined in a previous study [32] by the ratio of the confinement strength ω z over the depth of the Gaussian potential D as…”
Section: A Theoretical Modelmentioning
confidence: 99%
“…In previous studies of this series [18,19,32,37] it has been demonstrated that a set of properly chosen Cartesian anisotropic Gaussian-type orbitals (c-aniGTOs) is the most convenient choice to correctly approximate the wavefunction of electrons confined in anisotropic potentials. A c-aniGTO basis set can be transformed into a set of eigenfunctions of the corresponding three-dimensional anisotropic harmonic oscillator [19].…”
Section: B Basis Setmentioning
confidence: 99%
See 3 more Smart Citations